PENGEMBANGAN PARIWISATA DALAM PERSPEKTIF COMMUNITY BASED TOURISM DI KAWASAN PARIWISATA UBUD - Ida Ayu Githa Girindra (Jurnal Administrasi Publik, 2023)
Successful tourist destinations around the world are currently facing tough challenges because of their own regional attractiveness, such as the Ubud Tourism Area. The development of tourism in Ubud encourages the emergence of congestion problems, lack of parking space, damage to culture and traffic violations and uncontrolled spatial planning. The aim of this research is to look at Ubud tourism management in the perspective of Community Based Tourism (CBT) on five dimensions: social, economic, political, environmental and cultural. This study uses a qualitative method with a descriptive approach. The results of this study indicate that CBT in Ubud supports the development of the economic, political and cultural dimensions, while the environmental and social dimensions have not been optimally accommodated because Ubud does not yet have the carrying capacity and tourists' understanding of Ubud's character as a cultural tourism area is low.